Legal and medical aspects of regular firearms us age by law enforcementagencies in Ukraine - Aleksandr Gurov; Vitaliy Shcherbak; Victor Sapielkin (Kazimierz Wielki University, 2018)
Background. Ukraine is one of few European countries where the law on the circulation of weapon is still not adopted. At present usage of firearms in this country is regulated by subordinate legislation. Events of the last years in Ukraine demonstrate extremely rapid growth of quantity of firearms among the civilian population. As a result for the last 5 years the quantity of cases of criminal firearms usage rose sharply. The objective. For the conductions of forensic examinations to make complex cross-disciplinary researches of elastic bullets of cartridges "Teren-12P". The results. The study of the bullets physical properties and microelement structure, digital computer modeling of shock and contact interaction with a target and laboratory researches of products distribution of a shot when firing from various distances in biological and non-biological simulators of flesh, study of the influence of various samples of clothes material on the volume and nature of damages, the morphological nature of skin wounds and of clothes material injuries, weight of a fire wound depending on the speed of bullets and distance of a shot have been made. The perspective directions of further researches of a fire wound for the solution of practical expert tasks are defined. Conclusion. Forensic medical expert researches on cases of firearms application in Ukraine including the nonlethal action of the one equipped with large-caliber cartridges with elastic bullets are of particular importance not only for investigation of resonant criminal proceedings, but also have important social and public value connected with material and moral compensation to the victims.